Analysis of Job Satisfaction Through Motivation, Leadership and Organizational Commitment - Christian, David; I Gede, I Gede Adiputra (Asean International Journal of Business, 2024)
This study aims to analyze the effect of motivation, leadership and organizational commitment on employee job satisfaction at PT Rittindo in Bekasi. This research was conducted using probability sampling method with simple random sampling type. Researchers distributed questionnaires to 92 employees of PT Rittindo. Data analysis using Smart PLS analysis. The results of the analysis concluded that motivation, leadership and organizational commitment have a significant effect on employee job satisfaction at PT Rittindo in Bekasi.